2012
DOI: 10.3390/ijms131215813
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage and Repair in Epithelium after Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) in humans, following hematoablative treatment, results in biological chimeras. In this case, the transplanted hematopoietic, immune cells and their derivatives can be considered the donor genotype, while the other tissues are the recipient genotype. The first sequel, which has been recognized in the development of chimerical organisms after allo-HSCT, is the graft versus host (GvH) reaction, in which the new developed immune cells from the graft re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…With the increase in the number of haematopoietic stem cell transplantations, more attention is being paid to the occurrence of post-transplantation tumour development. 79 A report published in 1999 that analysed data from more than 1000 patients who had undergone bone marrow transplantation showed that the incidence of secondary malignancies was about 3.5% at 10 years and 12.8% at 15 years, which was 3.8-fold higher than that of an age-matched control population. 10 A more recent update of this research published in 2008 indicated that compared with the age-matched control population, the incidence of secondary malignancies was increasing, with a longer follow-up time.…”
Section: Discussionmentioning
confidence: 99%
“…With the increase in the number of haematopoietic stem cell transplantations, more attention is being paid to the occurrence of post-transplantation tumour development. 79 A report published in 1999 that analysed data from more than 1000 patients who had undergone bone marrow transplantation showed that the incidence of secondary malignancies was about 3.5% at 10 years and 12.8% at 15 years, which was 3.8-fold higher than that of an age-matched control population. 10 A more recent update of this research published in 2008 indicated that compared with the age-matched control population, the incidence of secondary malignancies was increasing, with a longer follow-up time.…”
Section: Discussionmentioning
confidence: 99%
“…% tail DNA directly correlates with DNA break frequency and, as such, our data would indicate that both PBN and AA are capable of reducing the frequency of DNA breaks in H 2 O 2 -treated ADSCs. Genotoxic stress has been previously reported to trigger the differentiation of ADSCs into adipocytes [ 21 , 22 ] and complications in DNA damage and repair have been reported following allogeneic transplantation with stem cells [ 36 ]. Therefore, the basal levels of DNA damage in MSCs may affect their efficiency and therapeutic potential following transplantation.…”
Section: Discussionmentioning
confidence: 99%